Penerapan Behaviorisme Dalam Pesan Dakwah : Kajianterhadap Video “Momentum Besar Hidup Saya” Oleh Raim Laode - arfan, ahmad; Rayhan, Muhammad; Dwi Maharani, Nur Afni; qudratullah, qudratullah (Journal of Innovative and Creativity, 2026)
Overall, the combination of behaviorist theory and Islamic moral learning theory provides a more comprehensive understanding of how digital da'wah messages can influence a person's behavior. Stimuli in the form of verbal messages and personal narratives provide a powerful stimulus; responses emerge in the form of motivation and a desire to change; reinforcement arises from positive feelings after receiving the message; and motivation serves as a bridge between stimulus and response. This process then continues in the form of long-term moral habituation, resulting in stable behavioral change. Thus, digital da'wah, such as that carried out by Raim Laode, not only provides momentary inspiration but also has significant potential to shape the behavior, character, and morality of audiences through interconnected psychological and spiritual mechanisms. The integration of behaviorist theory and Islamic moral learning demonstrates that digital media can be an effective means of da'wah if managed well, combining the power of a heartfelt message, communicative delivery, and the presence of a preacher who serves as a moral role model for the audience.